FORMULASI MASKER GEL LIDAH BUAYA (Aloe Vera) UNTUK PENGENDALIAN BAKTERI Propionibacterium acnes - Irvan Shahrul Hidayat; Muhammad Nurul Fadel; Intan Adevia Rosnarita (Yayasan Nusantara Hasana Berdikari, 2025)
Acne (Acne vulgaris) is a common skin problem, especially among adolescents, with a prevalence reaching 80-85% in Indonesia. One of the main causes of acne is the bacteria Propionibacterium acnes. Acne treatment usually uses synthetic antibiotics, but long-term use can cause side effects and bacterial resistance. Alternative natural treatments are needed to address this problem. Aloe vera is known to have antibacterial, anti-inflammatory, and cell regeneration-accelerating properties, making it potentially useful in skin care products. The active ingredients of aloe vera, such as anthraquinones, saponins, and flavonoids, are effective in inhibiting the growth of Propionibacterium acnes. Peel-off gel masks were chosen as topical preparations because they are practical, have a cooling effect, and can increase the penetration of active ingredients. This study aims to develop a gel mask formulation with aloe vera extract and test its effectiveness in inhibiting the growth of Propionibacterium acnes bacteria. This study used a laboratory experimental method with a post-test only control group design. The formulas used included various concentrations of aloe vera extract (5%, 10%, and 15%) and a positive control using 1% clindamycin. Evaluation of the preparations included organoleptic tests, homogeneity, pH, viscosity, spreadability, adhesion, drying time, and antibacterial activity testing using the disc diffusion method. Antibacterial effectiveness testing was divided into 5 treatment groups. The inhibition zone test against Propionibacterium acnes was conducted to assess the effectiveness of each formulation. The test data were analyzed using the One Way ANOVA statistical method with SPSS 25 software to determine significant differences between groups. Antibacterial testing was conducted by disc diffusion. The results of the study on the aloe vera extract peel-off gel mask formulation showed good organoleptic physical quality, homogeneity, adhesiveness, and drying time of the preparation, while the viscosity and spreadability tests did not meet the requirements, and the pH test on formula F3 did not meet the pH requirements for mouthwash preparations. In the antibacterial activity test of the peel-off gel mask preparation, the inhibition zone values ​​were obtained at F0 2.23 mm; F1 4.8 mm; F2 6 mm; F3 7.2 mm; and the positive control 33.5 mm.